Employing Activity Theory Based Green Chemistry Experiments To Improve Chemistry Learning Among Matriculation Students - Kulandaisamy, Yvonne (2020)
The central role of laboratory work in learning of Science like Chemistry is fundamental. In learning Chemistry, the abstract concepts hinders students from relating their own experience of the concept and therefore unable to identify the importance of learning Chemistry. Effective instructional strategies are crucial for making abstract concepts more tangible. This study introduced the Activity Theory based Green Chemistry (ATGC) Experiments as a laboratory instructional strategy. Simultaneously, this study measured the effectiveness of ATGC Experiments on students’ understanding of Chemistry concepts, Chemistry laboratory learning environment and critical thinking skills.